The Development Media for Interactive Learning using Bots Api of Telegram Social Media on Harmonic Motion Materials for Class X of Senior High School - Kurniawan, Yudi; Connie, Connie; Nirwana, Nirwana (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to (1) Describe the feasibility of interactive learning media with Bot API Telegram social media on harmonic motion material to help students understand concepts and (2) Describe students' perceptions of the readability of Interactive learning media with Bot API Telegram social media on the harmonic motion material that has been developed. This study used the Research and Development (R&D) method with a 4D development model modified into 3D, namely define, design, and development. Data analysis techniques used in this study are quantitative and qualitative. The sample data used in this study were 60 class X students from 3 schools, namely SMAN 1 Bengkulu City, SMAN 5 Bengkulu City, and SMAN 8 Bengkulu City. The results obtained in this study indicate that Bot API is included in the very feasible category in the feasibility validity test by a team of experts with an average percentage of 91.75% so that API Bot developed can be used as a reference for additional teaching materials and produce perceptions. students with an average score percentage of 88.29%, which is in the very good category.